The TLR5 Agonist Flagellin Shapes Phenotypical and Functional Activation of Lung Mucosal Antigen Presenting Cells in Neonatal Mice - Sharma, Pankaj; Levy, Ofer; Dowling, David J. (Frontiers in Immunology, 2020)
Intranasal mucosal vaccines are an attractive approach to induce protective mucosal immune responses. Activation of lung antigen presenting cells (APCs), a phenotypically and functionally heterogeneous cell population located at distinct mucosal sites, may be key to the immunogenicity of such vaccines. Understanding responsiveness of newborn lung APCs to adjuvants may inform design of efficacious intranasal vaccines for early life, when most infections occur. Here, we characterized and phenoytped APCs from neonatal (7 days of life) and adult (6-8 weeks of age) mice. Neonatal mice demonstrated a relatively high abundance of alveolar macrophages (AMs), with lower percentages of plasmacytoid dendritic cells (pDCs), CD103+ (cDC1) and CD11b+ (cDC2) DCs. Furthermore, neonatal CD103+ and CD11b+ DC subsets demonstrated a significantly lower expression of maturation markers (CD40, CD80 and CD86) as compared to adult mice. Upon stimulation of lung APC subsets with a panel of pattern recognition receptor (PRR) agonists, including those engaging TLRs or STING, CD11c+ enriched cells from neonatal and adult mice lungs demonstrated distinct maturation profiles. Of the agonists tested, the TLR5 ligand, flagellin, was most effective at activating neonatal lung APCs, inducing significantly higher expression of maturation markers on CD103+ (cDC1) and CD11b+ (cDC2) subsets. Intranasal administration of flagellin induced a distinct migration of CD103+ and CD11b+ DC subsets to the mediastinal lymph nodes (mLNs) of neonatal mice. Overall, these findings highlight age-specific differences in the maturation and responsiveness of lung APC subsets to different PRR agonists. The unique efficacy of flagellin in enhancing lung APC activity suggests that it may serve as an effective adjuvant for early life mucosal vaccines.